Expert judgment and uncertainty regarding the protection of imperiled species. Issue 3 (14th December 2016) - Heeren, Alexander; Karns, Gabriel; Bruskotter, Jeremy; Toman, Eric; Wilson, Robyn; Szarek, Harmony
Abstract: Decisions concerning the appropriate listing status of species under the U.S. Endangered Species Act (ESA) can be controversial even among conservationists. These decisions may determine whether a species persists in the near term and have long‐lasting social and political ramifications. Given the ESA's mandate that such decisions be based on the best available science, it is important to examine what factors contribute to experts' judgments concerning the listing of species. We examined how a variety of factors (such as risk perception, value orientations, and norms) influenced experts' judgments concerning the appropriate listing status of the grizzly bear (Ursus arctos horribilis) population in the Greater Yellowstone Ecosystem. Experts were invited to complete an online survey examining their perceptions of the threats grizzly bears face and their listing recommendation. Although experts' assessments of the threats to this species were strongly correlated with their recommendations for listing status, this relationship did not exist when other cognitive factors were included in the model. Specifically, values related to human use of wildlife and norms (i.e., a respondent's expectation of peers' assessments) were most influential in listing status recommendations. These results suggest that experts' decisions about listing, like all human decisions, are subject to the use of heuristics (i.e., decision shortcuts). An understanding of how heuristics and related biases affect decisions under uncertainty can help inform decision making about threatened and endangered species and may be useful in designing effective processes for protection of imperiled species.